The impact of man on the morphodynamics of the Huelva coast (SW Spain) - Rodríguez-ramírez, A.; Morales, J.A.; Delgado, I.; Cantano, M. (Journal of Iberian Geology, 2008)
The Huelva coast is composed by large sandy beaches and spits, only interrupted by the presence of the estuarine mouths of the Guadiana, Piedras, Tinto-Odiel and Guadalquivir which are in an advanced state of sediment infilling. The morphology and processes of the Huelva coast are mainly linked to tidal regime, wave action, coastal-drift currents, fluvial dynamics, climatic change and anthropogenic activity. In the last five decades anthropogenic activity has modified the natural dynamics by the construction of jetties, docks, harbour and coastal developments. The main consequences have been the interruption of the sedimentary bypassing caused by an active west-to-east littoral drift, the modification of the tidal regime, the wave refraction-diffraction scheme and the intensification of the littoral erosive processes. All these effects will increase with the slow sea-level rise, close to 0.6 cm per year, which will induce a higher efficacy of the erosional events. A future retreat of about 10-15 m of the coastline is estimated.
Keywords: Morphodynamics; Anthropogenic influence; Coast; Huelva; SW Spain